Corynebacterium diphtheriae Virulence Analyses Using a Caenorhabditis elegans Model. Issue 1 (13th July 2020) - Chen, Yi‐Wei; Ton‐That, Hung
Abstract: Corynebacterium diphtheriae is the leading cause of pharyngeal diphtheria, a respiratory disease characterized by formation of a pseudomembrane at the site of infection. Although outbreaks of C. diphtheriae infections are rare nowadays, the emergence of multidrug‐resistant C. diphtheriae strains is one of the most significant public health concerns worldwide. Although C. diphtheriae has been studied for more than a century and diphtheria toxin and pili have been identified as major virulence factors, little is known about factors involved in bacterial colonization and development of disease. Here, we describe the utilization of Caenorhabditis elegans as a cost‐effective, versatile model of infection to evaluate C. diphtheriae virulence. We provide detailed protocols for nematode synchronization and for evaluation of nematode survival and formation of a deformed anal region induced by C. diphtheriae infection. These protocols will permit future high‐throughput screenings of virulence factors in C. diphtheriae and advance our knowledge of C. diphtheriae pathogenesis. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Synchronization of nematodes Basic Protocol 2 : Assay for nematode survival following C. diphtheriae infection Basic Protocol 3 : Assays for bacterial colonization and formation of deformed anal region